Editorial for Special Issue “Casting Alloy Design and Characterization” - Eleani Maria da Costa; Carlos Alexandre dos Santos (Metals)
Solidification, the genesis of metallic materials, is a complex phenomenon encompassing fluid flow, heat transfer, phase transformation, liquid–solid interface, solute redistribution, gas trapping, and others [...]